Modern strategy on managing patients with stomach pre-cancer - L. B. Lazebnik; E. A. Lyalukova; G. V. Belova; I. V. Dolgalev; N. V. Korochanskaya; V. K. Kosenok; A. S. Lyalukova; E. V. Onuchina; M. M. Petrova; L. V. Prokhorova; A. S. Sarsenbaeva (Лечащий Врач, 2021)
The review summarize existing international recommendations for managing patients with atrophic gastritis, intestinal metaplasia and gastric dysplasia. It is shown that patients with chronic anthropic gastritis or intestinal metaplasia have an increased risk of stomach adenocarcinoma development. Helicobacter pylori eradication tends to relieve indications of chronic nonatrophic gastritis and can lead to partial regression of atrophic gastritis, and reduces the risk of stomach cancer development.